Fructo-oligosaccharides and intestinal barrier function in a methionine–choline-deficient mouse model of nonalcoholic steatohepatitis - Matsumoto, Kotaro; Ichimura, Mayuko; Tsuneyama, Koichi; Moritoki, Yuki; Tsunashima, Hiromichi; Omagari, Katsuhisa; Hara, Masumi; Yasuda, Ichiro; Miyakawa, Hiroshi; Kikuchi, Kentaro (PLOS ONE, 2017)
Impairments in intestinal barrier function, epithelial mucins, and tight junction proteins have been reported to be associated with nonalcoholic steatohepatitis. Prebiotic fructo-oligosaccharides restore balance in the gastrointestinal microbiome. This study was conducted to determine the effects of dietary fructo-oligosaccharides on intestinal barrier function and steatohepatitis in methionine–choline-deficient mice. Three groups of 12-week-old male C57BL/6J mice were studied for 3 weeks; specifically, mice were fed a methionine–choline-deficient diet, a methionine–choline-deficient diet plus 5% fructo-oligosaccharides in water, or a normal control diet. Fecal bacteria, short-chain fatty acids, and immunoglobulin A (IgA) levels were investigated. Histological and immunohistochemical examinations were performed using mice livers for CD14 and Toll-like receptor-4 (TLR4) expression and intestinal tissue samples for IgA and zonula occludens-1 expression in epithelial tight junctions. The methionine–choline-deficient mice administered 5% fructo-oligosaccharides maintained a normal gastrointestinal microbiome, whereas methionine–choline-deficient mice without prebiotic supplementation displayed increases in Clostridium cluster XI and subcluster XIVa populations and a reduction in Lactobacillales spp. counts. Methionine–choline-deficient mice given 5% fructo-oligosaccharides exhibited significantly decreased hepatic steatosis (p = 0.003), decreased liver inflammation (p = 0.005), a decreased proportion of CD14-positive Kupffer cells (p = 0.01), decreased expression of TLR4 (p = 0.04), and increases in fecal short-chain fatty acid and IgA concentrations (p < 0.04) compared with the findings in methionine–choline-deficient mice that were not administered this prebiotic. This study illustrated that in the methionine–choline-deficient mouse model, dietary fructo-oligosaccharides can restore normal gastrointestinal microflora and normal intestinal epithelial barrier function, and decrease steatohepatitis. The findings support the role of prebiotics, such as fructo-oligosaccharides, in maintaining a normal gastrointestinal microbiome; they also support the need for further studies on preventing or treating nonalcoholic steatohepatitis using dietary fructo-oligosaccharides.